Особливості формування інвестиційного портфеля та напрями його оптимізації - Петраш, О. П. (Ways to Improve Construction Efficiency, 2012)
The paper deals with approaches to building an investment portfolio, its main parameters and their influence on the activity of investors of the global financial crisis.